2020
DOI: 10.1039/d0ob00216j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of artemisinic acid derived glycoconjugates and their anticancer studies

Abstract: Twenty-four artemisinic acid glycoconjugate hybrids were synthesized using click reaction and evaluated for their anticancer activities against the MCF7 cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…3) were synthesized as per reported literature methods and their spectral data were found to be consistent with the reported literature data. 15,20,21 The stereochemistries of the anomeric configurations of the azido sugars 5a-f were assigned as the β-configurations on the basis of comparison with reported data 20 as well as their coupling constants in the 1 H NMR (nuclear magnetic resonance) spectra. In general, the anomeric proton of the azido sugars appeared as a doublet integrated to one proton at 4.61-4.98 ppm in the 1 H NMR spectra with a coupling constant in the range of 8.5-8.8 Hz, which unequivocally proves that the azide groups are β-oriented.…”
Section: Synthesis and Characterization Of The Synthesized Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…3) were synthesized as per reported literature methods and their spectral data were found to be consistent with the reported literature data. 15,20,21 The stereochemistries of the anomeric configurations of the azido sugars 5a-f were assigned as the β-configurations on the basis of comparison with reported data 20 as well as their coupling constants in the 1 H NMR (nuclear magnetic resonance) spectra. In general, the anomeric proton of the azido sugars appeared as a doublet integrated to one proton at 4.61-4.98 ppm in the 1 H NMR spectra with a coupling constant in the range of 8.5-8.8 Hz, which unequivocally proves that the azide groups are β-oriented.…”
Section: Synthesis and Characterization Of The Synthesized Compoundsmentioning
confidence: 99%
“…It has also been reported that the conjugation of a carbohydrate scaffold to naturally occurring bioactive molecules has led to enhanced bioactivity and manifestation of superior biological properties such as solubility, stability, and bioactivity compared to the parent molecule. [15][16][17] Therefore, glycoconjugates of bioactive natural products can be ideal candidates for efficacious therapeutic agents. The hypervalent nature of sugar assists the drug molecule to reach target cells, thus playing a major role in the drug delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…Bhattacharya and co-workers produced a family of O -artemisinic acid and N- artemisinic acid glycohybrids via CuAAC coupling of individual sugar azides with propargyl O -artemisinic acid ester under standard click conditions in appreciable yields . The resulting glycohybrid analogues of artemisinic acid were evaluated for their anticancer activity.…”
Section: Application Of Carbo-cuaac Click Chemistry In Drug Discovery...mentioning
confidence: 99%
“…CuAAC click chemistry mediated artemisinic acid derived glycohybrids ( 1086 and 1087 ) with promising anticancer activities …”
Section: Application Of Carbo-cuaac Click Chemistry In Drug Discovery...mentioning
confidence: 99%
“…Since the peroxide bridge present in artemisinins is the main pharmacophore responsible for both antiplasmodial In another study [65], glycoconjugate derivatives of artemisinic acid were synthesized and anticancer properties were studied. It was found that all artemisinic acid glycoconjugates were able to inhibit the growth of MCF7, however, showed moderate cytotoxicity (Fig.…”
Section: Modificationsmentioning
confidence: 99%